FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN KREDIT USAHA KELOMPOK DALAM PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) DI KECAMATAN BANGUN REJO KABUPATEN LAMPUNG TENGAH - Kholis Meizari; R Hanung Ismono; Achdiansyah Soelaiman (Lampung University, 2015)
This study aims to analyze:(1) the implementation process of funds distribution in PUAP Program at Gapoktan Bangun Rejo, Central Lampung, (2) the percentage of capital repayment level of PUAP, (3) the factors that affect credit refund level of PUAP. This research was conducted at Bangun Rejo, Central Lampung based on purposive. Amount of sample were 79 respondents whichconsists of 41people with current loan repayment and 38 people with non-current loan repayment. The first and second purpose were analyzed by using descriptively while and the third were analyzed by using logit method. The result showed that(1) implementation process of funds distribution in PUAP Program for the member of farmers group at Gapoktan Tanjung Pandan or Cimarias have the same requirements and mechanisms, and the differences between them were amount of interest rate, sanctions and letter of borrowing stemped 6000,(2) overall, credit refund level of PUAP at Tanjung Pandan in every step revolving has fluent loan quality with the percentage of 100%. While credit refund level at Cimarias has loan quality in specific concern with the percentage of 72.6% at first step and 51.66% at second step, this credit refund level also has the jammed loan quality 27.4% at first step and 48.33% at second step, (3) the factors that affected the level of group capital repayment of PUAP were the level of education, age, family income and the knowledge of PUAP. Key words: credit refund, gapoktan, PUAP